Use of AI in learning Arabic language by non-Arabic speakers - Garba, Mahmud Abubakar; Hassan, Abd Rauf (Research and Scientific Innovation Society, 2024)
The integration of artificial intelligence (AI) into learning the Arabic language for non-Arabic speakers represents a notable advancement in educational technology. This research explores the advantages and challenges of using AI applications to enhance Arabic language learning by non-Arabic native speakers. These applications include the ArabicPod101 as a means of listening skills, the Lingbe as a means of speaking skills, the Duolingo as a means of reading skills, and the Scribe as a means of writing skill. The use of these applications will facilitate the learning of Arabic for non-Arabic speakers. Adapting the description method, with ten students of the 100-level Department of Arabic Language at Umaru Musa Yar'adua Katsina, Nigeria, a questionnaire was used to collect data from the participants after the researchers taught them some features of these AI applications in learning listening, speaking, reading, and writing skills. The results indicate that the participants agreed on the importance of these applications in enhancing the learning of four language skills. It would be a great idea if these applications were incorporated into teaching Arabic to non-Arabic speakers.